Manajemen Humas Pendidikan Dalam Upaya Pencitraan Sekolah di Sekolah Menengah Kejuruan - Fifin Priandono (Institut Agama Islam Negeri Bengkulu, 2019)
Abstract: Parent's Hegemony Towards Children as a Trigger for Violence in Educating ChildrenEducation Institute is grown and developed by, through the initiative, and for the shake of communities’ demands, so that the existence of public relations management on the development of the Education Institute becomes important. This article aims to provide concepts of techniques of public relations management in the development of the Education Institute in Indonesia, as well as how to apply it, problems faced, and how to solve the problems. The results of this study are expected to be able to broaden insight of managers of the Education Institute in order to make public relations programs effectively and efficiently operate and to realize the development of the Education Institute in a broad sense. Public relations planning in an effort to improve the school image in Vocational School involves all school managers by scheduling all good and detailed public relations and planning activities through the annual program meeting. the implementation of public relations at Vocational School is carried out in accordance with the plan where the public relations task informs all activities in the school to be known to the public.Abstrak : Manajemen Humas Pendidikan Dalam Upaya Pencitraan Sekolah di Sekolah Menengah Kejuruan Lembaga Pendidikan ditumbuhkan dan dikembangkan oleh, melalui inisiatif, dan untuk tuntutan masyarakat, sehingga keberadaan manajemen hubungan masyarakat pada pengembangan Lembaga Pendidikan menjadi penting. Artikel ini bertujuan untuk memberikan konsep teknik manajemen hubungan masyarakat dalam pengembangan Institut Pendidikan di Indonesia, serta bagaimana menerapkannya, masalah yang dihadapi, dan bagaimana menyelesaikan masalah tersebut. Hasil penelitian ini diharapkan dapat memperluas wawasan para pengelola Lembaga Pendidikan agar menjadikan program PR berjalan efektif dan efisien, serta mewujudkan pengembangan Lembaga Pendidikan dalam arti luas. Perencanaan hubungan masyarakat dalam upaya meningkatkan citra sekolah di Sekolah Kejuruan melibatkan semua manajer sekolah dengan menjadwalkan semua hubungan masyarakat dan kegiatan perencanaan yang baik dan terperinci melalui pertemuan program tahunan. pelaksanaan hubungan masyarakat di Sekolah Kejuruan dilakukan sesuai dengan rencana di mana tugas hubungan masyarakat menginformasikan semua kegiatan di sekolah untuk diketahui publik.